Water Level Monitoring System for Paddy Field Irrigation - GUNALAN A/L P BALAN; Dr Faiz Asraf Bin Saparudin (Progress in Engineering Application and Technology, 2023)
Acres of paddy field in Sawah Sungai Balang have own by different owners. The issue found on the paddy field Sungai Balang is the uneven ground, which is getting worse to overflood the plot of paddy fields. Farmers and owners of the plot hard to monitor manually the water level in the large acre of paddy fields. The solution may be found in accessing and making use of real time information in water level monitoring. The irrigation pattern requires the suitability of water level for paddy field growth process. The Water Level Monitoring System is helpful to the farmers and owner of the plots knowing the actual amount of water from the soil and making it a user-friendly system. This research develops a water level monitoring system for irrigation systems with NodeMCU module to send the water level sensors data to cloud. With this communication technology, can be used to send data from the field to the cloud, allowing farmers and owners of the plot to leverage the data and improve their activities.